Research on the Optimization of the Undergraduate Talent Training Program for Primary Education in Fujian Province's Colleges and Universities under the Background of "Teacher Education Program Accreditation" - Zhang Heng; Zhou Limin (Journal of Exploration of Vocational Education, 2025)
Abstract This study, set against the backdrop of Teacher Education Program Accreditation, employs literature review and text analysis methods to examine the undergraduate talent training programs of six universities in Fujian Province offering primary education majors. The research identifies structural contradictions within these programs and proposes optimization strategies. The findings reveal a convergence in the design of training objectives, with insufficient integration of regional characteristics; an imbalanced curriculum structure with weak practical support; and a lack of systematic organization and reflective components in educational practice. In response, this study suggests enhancing localization and diversifying the reconstruction of training objectives, optimizing the curriculum by building a “theory–practice–reflection” closed-loop system, and deepening reforms in educational practice to strengthen reflection and research competencies. Looking ahead, undergraduate talent training in primary education in Fujian Province should further align with the strategic orientation of Teacher Education Program Accreditation, while exploring innovative paths in digital transformation and cross-regional collaboration. These efforts aim to provide sustained momentum for the high-quality development of teacher education in China.